Bimbingan Teknis Pembuatan Google Sites: (Pengabdian Masyarakat Berbasis Inklusi Sosial pada Binaan Dinas Perpustakaan dan Arsip Kota Salatiga Komunitas Wirausaha) - Hermawan, Anton; Koerniawati, Tintien; Lestari, Elizabeth Sri; Narendra, Albertoes Pramoekti (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
This community empowerment activity was carried out in the entrepreneurial community supported by the Salatiga City Library and Archives Service. Based on the results of community service activities with the theme "Technical Guidance on Website Development Using Googlesite (Social Inclusion-Based Community Service at the Assistance of the Salatiga City Library and Archives Service) Entrepreneurial Community" which has been carried out, it can be concluded as follows: 1) Participants already have additional information about marketing through online media and how to use it to market the products of small and medium businesses in Salatiga City through the Google site. 2) The participants of small and medium businesses get a management technique method for marketing products through online media. Small and medium businesses in Salatiga City know how to do simple bookkeeping.